Advances and Opportunities of CRISPR/Cas Technology in Bioengineering Non-conventional Yeasts - Shan, Lu; Dai, Zongjie; Wang, Qinhong (Frontiers in Bioengineering and Biotechnology, 2021)
Non-conventional yeasts have attracted a growing interest on account of their excellent characteristics. In recent years, the emerging of CRISPR/Cas technology has improved the efficiency and accuracy of genome editing. Utilizing the advantages of CRISPR/Cas in bioengineering of non-conventional yeasts, quite a few advancements have been made. Due to the diversity in their genetic background, the ways for building a functional CRISPR/Cas system of various species non-conventional yeasts were also species-specific. Herein, we have summarized the different strategies for optimizing CRISPR/Cas systems in different non-conventional yeasts and their biotechnological applications in the construction of cell factories. In addition, we have proposed some potential directions for broadening and improving the application of CRISPR/Cas technology in non-conventional yeasts.